A strength-oriented exercise session required more recovery time than a power-oriented exercise session with equal work - Helland, C.; Midttun, M.; Saeland, F.; Haugvad, L.; Schäfer Olstad, D.; Solberg, P. A.; Paulsen, G. (PeerJ, 2020)
The present randomized cross-over controlled study aimed to compare the rate of recovery from a strength-oriented exercise session vs. a power-oriented session with equal work. Sixteen strength-trained individuals conducted one strength-oriented session (five repetitions maximum (RM)) and one power-oriented session (50% of 5RM) in randomized order. Squat jump (SJ), countermovement jump (CMJ), 20-m sprint, and squat and bench press peak power and estimated 1RMs were combined with measures of rate of perceived exertion (RPE) and perceived recovery status (PRS), before, immediately after and 24 and 48 h after exercise. Both sessions induced trivial to moderate performance decrements in all variables. Small reductions in CMJ height were observed immediately after both the strength-oriented session (7 ± 6%) and power-oriented session (5 ± 5%). Between 24 and 48 h after both sessions CMJ and SJ heights and 20 m sprint were back to baseline. However, in contrast to the power-oriented session, recovery was not complete 48 h after the strength-oriented session, as indicated by greater impairments in CMJ eccentric and concentric peak forces, SJ rate of force development (RFD) and squat peak power. In agreement with the objective performance measurements, RPE and PRS ratings demonstrated that the strength-oriented session was experienced more strenuous than the power-oriented session. However, these subjective measurements agreed poorly with performance measurements at the individual level. In conclusion, we observed a larger degree of neuromuscular impairment and longer recovery times after a strength-oriented session than after a power-oriented session with equal total work, measured by both objective and subjective assessments. Nonetheless, most differences were small or trivial after either session. It appears necessary to combine several tests and within-test analyses (e.g., CMJ height, power and force) to reveal such differences. Objective and subjective assessments of fatigue and recovery cannot be used interchangeably; rather they should be combined to give a meaningful status for an individual in the days after a resistance exercise session.